2015
DOI: 10.1039/c5cp04273a
|View full text |Cite
|
Sign up to set email alerts
|

Nucleobases tagged to gold nanoclusters cause a mechanistic crossover in the oxidation of CO

Abstract: DNA is considered as a programmable building block for the assembly of nanomaterials that play a significant role in modern day nanotechnology and catalysis. In this work, density functional theory (DFT) is used to explore the possible application of complexes of DNA bases (adenine (A), thymine (T), guanine (G), and cytosine (C)) and their size expanded (x) counterparts with Au3 gold clusters as a model catalyst system for oxidation of CO to CO2. We investigate how the catalytic potential of the Au3 cluster is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 66 publications
(147 reference statements)
0
6
0
Order By: Relevance
“…The electronic charge on the NP increases with respect to an increase in the number of EP molecules adsorbed, which is limited by the maximum number of EP molecules that can directly interact with a given NP. It has been shown previously that adding an electron to metal clusters and tagging of small molecules such as DNA bases have a significant electronic effect on the physicochemical properties of metal nanoclusters. , This clearly suggests that model chemistries chosen for studying reactions catalyzed by NPs should also appropriately consider the environment of the system. Molecular dynamics simulations can effectively be used to generate initial model systems for further QM or DFT calculations.…”
Section: Resultsmentioning
confidence: 99%
“…The electronic charge on the NP increases with respect to an increase in the number of EP molecules adsorbed, which is limited by the maximum number of EP molecules that can directly interact with a given NP. It has been shown previously that adding an electron to metal clusters and tagging of small molecules such as DNA bases have a significant electronic effect on the physicochemical properties of metal nanoclusters. , This clearly suggests that model chemistries chosen for studying reactions catalyzed by NPs should also appropriately consider the environment of the system. Molecular dynamics simulations can effectively be used to generate initial model systems for further QM or DFT calculations.…”
Section: Resultsmentioning
confidence: 99%
“…It was vastly reported in earlier studies that the L–H mechanism is more promising for the CO oxidation reaction. , Therefore, we decided to proceed with the L–H mechanism which is divided into two half-reactions (1) CO + O 2 → CO 2 (involves the splitting of the side-on superoxo bond/breaking of the Ni–O bond) and (2) CO + O → CO 2 (the CO oxidation barrier depends on the breaking of the Ni–O bond) to perform CO oxidation over representative systems. Among the representative systems considered to perform CO oxidation, the flawless reaction profile is inspected for the Ni 12 Cu cluster with the lowest activation barrier 1.11 eV ( E a1 ) and 0.84 eV ( E a2 ) for the first and second half-reactions, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The M06 functional has been demonstrated to be a useful functional for applications in transition‐metal‐containing systems . In particular, we have recently shown that DFT calculations with the M06 functional is suitable for the study of chemical reactions on Au NCs . Benchmark calculations using the left‐eigenstate complete renormalized‐coupled cluster method with singles, doubles, and noniterative triples (CR‐CC(2,3)) for the reaction on Au NCs showed that M06 and B3LYP work well for the activation energy barrier, whereas B3LYP overestimates the reaction energy .…”
Section: Computational Detailsmentioning
confidence: 99%